2000
DOI: 10.1590/s0103-84782000000500018
|View full text |Cite
|
Sign up to set email alerts
|

Contagem bacteriana da superfície de tetas de vacas submetidas a diferentes processos de higienização, incluindo a ordenha manual com participação do bezerro para estimular a descida do leite

Abstract: A pele da teta é uma das principais fontes de contaminação microbiana do leite cru, além de ser uma fonte de infecção da glândula mamária. Este estudo comparou diferentes métodos de preparação do úbere, incluindo a participação do bezerro para estimular a descida do leite, em relação à contaminação microbiana da pele da teta. Um experimento com 36 vacas ordenhadas mecanicamente foi conduzido para comparar três procedimentos (A, B, C) de preparação do úbere. Duas tetas de cada vaca foram amostradas para contage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
3
0
15
Order By: Relevance
“…Milk production requires sufficient drinking water to meet animal needs, cleaning and sanitizing the teats, equipment and facilities (Brito, Brito, & Verneque, 2000). In agreement with Guerreiro, Machado, Braga, Gasparino and Franzener (2005), environmental sources of milk contamination include water used for cleaning equipment and other tasks.…”
Section: Resultsmentioning
confidence: 82%
“…Milk production requires sufficient drinking water to meet animal needs, cleaning and sanitizing the teats, equipment and facilities (Brito, Brito, & Verneque, 2000). In agreement with Guerreiro, Machado, Braga, Gasparino and Franzener (2005), environmental sources of milk contamination include water used for cleaning equipment and other tasks.…”
Section: Resultsmentioning
confidence: 82%
“…As contagens de microrganismos aeróbios mesófilos nos tetos após o bezerro mamar demonstraram um pequeno aumento no grau de contaminação, que pode ser reduzido por meio do pré-dipping (BRITO; BRITO;VERNEQUE, 2000). O bezerro foi útil em situações de ordenha nos piquetes, observadas nesse estudo, onde não há instalações adequadas e água, auxiliando na eliminação dos primeiros jatos e na remoção do excesso de matéria orgânica dos tetos, que prejudicaria a ação do cloro no pré-dipping.…”
Section: Resultsunclassified
“…The percentage of positive microbiological examinations was greater for the samples in which milking was performed with the presence of the calf. According to Brito et al (2000), sucking by the calf promotes an increase in the colonization of microorganisms from the oral cavity in the skin of the teats; nevertheless, Oliveira et al (2011) affirmed that this procedure may reduce the rates of mastitis due to the removal of residual milk from the mammary gland and the antimicrobial action of the saliva. In addition, these authors observed that the feeding of animals during milking contributed to the increase in the occurrence of infection in cows from Minas Gerais (Souza et al 2005) and Pernambuco (Oliveira et al 2012) since soon after the milking, the teat sphincter remains open, favoring the entrance of environmental pathogens.…”
Section: Discussionmentioning
confidence: 99%